Life and death during the first six months of the COVID-19 pandemic: An analysis of cross-country differences in changes in quantity and quality of life - Lykke E. Andersen; Alejandra Gonzales Rocabado (Institute for Advanced Development Studies (INESAD), 2020)
This study carries out a cross-country analysis of changes in quantity and quality of life during the first six months of the COVID-19 pandemic (11 March to 11 September 2020) for 124 countries. Changes in quantity of life are measured as life years lost to COVID-19, including excess deaths not officially reported as COVID-19 deaths. Changes in quality of life are proxied by the average change in daily mobility, compared to a pre-COVID baseline. We find a significant negative correlation between the two, meaning that the countries with the biggest reductions in mobility are also the countries with the biggest losses of life years. We calculate that about 15 million life years were lost during the first six months of the pandemic, corresponding to 0.006% of all expected life years. For comparison, at least three times more life years are lost every six months due to children dying of diarrhea. About 28 million life years are created every day from babies being born, so the first six months of the pandemic set us back about 14 hours in terms of quantity of life. The setbacks in terms of quality of life are several orders of magnitude larger. Some countries have suffered more than a 50% reduction in mobility sustained over half a year, with devastating effects on many aspects of quality of life. Globally, the equivalent of 400 million full-time jobs were lost. GDP is estimated to have been set back about three years, poverty about five years, and the tourism industry about 20 years. The already large inequalities in access to quality education have been further widened, leaving hundreds of millions of disadvantaged children farther behind. Even countries that have managed the pandemic relatively well are suffering large economic contractions due to the negative spill-over effects from other countries. We still have a long way to go before this pandemic is over, and we urgently need to course-correct in order not to cause even more harm than has already been done. The paper provides a series of recommendations on what needs to be done to minimize total harm.
Keywords: H12; I14; I18; I38; 330; COVID-19; pandemic; life years; mobility; quality of life